What Drives SMEs’ Financial Sustainability in the Digital Era? - Amir Hamzah (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This study aims to examine the influence of financial literacy, accounting literacy, mental accounting, access to finance, innovation, and digital transformation on the financial sustainability of small and medium-sized enterprises (SMEs). The research employed a quantitative approach using a survey distributed to 229 SME owners. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results revealed that financial literacy, access to finance, innovation, and digital transformation had a positive and significant effect on SMEs’ financial sustainability. In contrast, accounting literacy showed a significant negative relationship, while mental accounting was found to have no significant impact. These findings indicate that improving financial knowledge, financing accessibility, innovation capacity, and digital adoption plays a crucial role in enhancing the financial resilience and sustainability of SMEs in the digital era. The study contributes to the growing body of knowledge on SME financial management and provides practical implications for policymakers, financial institutions, and SME practitioners in developing effective strategies for sustainable business growth. Keywords: Access to finance; Digital transformation; Financial literacy; Financial sustainability; Innovation